The Effect of Problem-Based Digital Educational Technology on Students’ Achievement and Creativity in Chemistry Learning - Minglan Hou; I Wayan Santyasa; Gede Rasben Dantes (Universitas Pendidikan Mandalika, 2026)
This study aims to examine the effectiveness of problem-based digital learning in enhancing students’ chemistry achievement and creativity. A quasi-experimental design with pretest–posttest control groups was employed. The participants were second-year undergraduate chemistry students selected through purposive sampling to ensure comparable academic backgrounds. Two intact classes were assigned as the experimental and control groups to maintain ecological validity. The research instruments included a chemistry achievement test, a chemistry creativity scale, and a learning behavior observation sheet. Data were analyzed using analysis of covariance (ANCOVA), multivariate analysis of variance (MANOVA), and thematic analysis for qualitative data. The results indicate that problem-based digital learning significantly improves students’ knowledge application, problem-solving skills, and chemistry creativity, particularly in terms of the uniqueness of experimental design, flexibility in solution optimization, and cross-context knowledge transfer. However, no significant difference was found between the two groups in the mastery of basic chemical knowledge. These findings suggest that chemistry instruction in higher education should move beyond the mere transmission of concepts toward problem-based digital learning that emphasizes application, problem solving, and creativity. The integration of authentic problems with virtual laboratory environments enables students to design experiments, test solutions, and transfer knowledge across contexts. In this approach, lecturers function as facilitators, while digital tools serve as cognitive instruments that bridge theoretical understanding and innovative chemical practice.